Cell division in Corynebacterineae - Donovan, Catriona; Bramkamp, Marc (Frontiers in Microbiology, 2014)
Bacterial cells must coordinate a number of events during the cell cycle. Spatio-temporal regulation of bacterial cytokinesis is indispensable for the production of viable, genetically identical offspring. In many rod-shaped bacteria, precise midcell assembly of the division machinery relies on inhibitory systems such as Min and Noc. In rod-shaped Actinobacteria, for example Corynebacterium glutamicum and Mycobacterium tuberculosis, the divisome assembles in the proximity of the midcell region, however more spatial flexibility is observed compared to Escherichia coli and Bacillus subtilis. Actinobacteria represent a group of bacteria that spatially regulate cytokinesis in the absence of recognizable Min and Noc homologs. The key cell division steps in E. coli and B. subtilis have been subject to intensive study and are well understood. In comparison, only a minimal set of positive and negative regulators of cytokinesis are known in Actinobacteria. Nonetheless, the timing of cytokinesis and the placement of the division septum is coordinated with growth as well as initiation of chromosome replication and segregation. We summarize here the current knowledge on cytokinesis and division site selection in the Actinobacteria suborder Corynebacterineae.